On A Subclass of Harmonic Univalent Funtions Associated with the Differential Operator - Ravindar, B; Bharavi Sharma, R (International Journal of Engineering and Technology, 2018)
In this paper, a new subclass of harmonic univalent functions in the unit disk Â is introduced using a differential operator. Also the coefficient estimates, convolution conditions, extreme points and convex combinations are obtained.Â Â